A glass powder, its preparation method and application
By adjusting the composition and sintering process of glass powder and changing the glass network structure, the problem of high blackness L value of existing automotive glass inks is solved, and the preparation and visual unified effect of low-black inks is achieved.
Patent Information
- Application Number
- CN202411912037.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
The blackness L value of existing automotive glass inks is high, and cannot meet the requirements of low blackness, which affects the visual effect of the printed materials.
By adjusting the ratio of Bi2O3/B2O3 and Bi2O3/SiO2 and the sintering process, the glass network structure is changed, thereby affecting the blackness and density of the ink. The specific composition includes 20-30 parts of B2O3, 30-40 parts of Bi2O3, 20-30 parts of SiO2, 2-6 parts of K2O, 10-15 parts of BaO, and 3-7 parts of MgO.
The preparation of low-black glass ink is achieved, with a blackness L value less than 2, and the combination with organic integrated black ink perfectly presents a uniform color, achieving a visual unified effect.
Smart Images

Figure BDA0005205942270000071 
Figure BDA0005205942270000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inks, and in particular relates to a glass powder and a preparation method thereof, and application of the glass powder in preparing low-blackness glass ink. Background Art
[0002] Automotive glass ink refers to the ink used on the edges of automotive tempered glass to effectively reduce the transmittance of ultraviolet rays, prevent chemical changes in the glue used to bond the glass and the car body, and at the same time shield the conductive silver paste to give the car an aesthetic effect. When preparing this ink, lead-free low-melting point glass is usually used. This glass is composed of low-melting point glass powder, inorganic black pigment and organic varnish. Among them, low-melting point glass powder is the key component, which determines the sintering temperature, color development and chemical stability of the ink. Low-black automotive glass ink can provide more detailed and realistic patterns and texts, and enhance the visual effect of printed products. This is because low-blackness high-temperature sintering ink needs to be screen-printed with organic integrated black ink after sintering. The blackness of the sintered ink is close to that of the organic integrated black ink, which is conducive to improving the clarity and visual effect of the printed product. However, the blackness of the existing automotive glass inks does not meet the requirements.
[0003] Prior art CN 111333335 B discloses a highly acid-resistant automotive glass ink and its preparation method. In order to improve the acid resistance of the glass ink, the invention adopts a two-step method to melt the acid-resistant glass powder. First, the precursor microcrystalline powder is pre-melted, and then the appropriate types and proportions of oxides and elements are added through appropriate batch materials. After the glass powder formed by the secondary melting is sintered in the ink, a considerable amount of silicon dioxide components will be enriched on the surface of the ink. The enrichment of silicon dioxide components improves the density of the network structure on the surface of the ink and greatly improves the acid resistance of the ink. However, the blackness L value of the ink is relatively high.
[0004] Prior art CN 115895332 B discloses a smooth low-blackness glass high-temperature ink and its preparation method and application, the ink includes glass powder, carrier resin, inorganic copper-chromium-cobalt black, nano-sphere silicon powder, solvent and additives, because the glass powder can melt at 600-700°C, and then can be fused with the glass material, and under the action of the molecular covalent bonds of the glass powder, the ink has good density and excellent acid resistance; and by adding nano-sphere silicon powder to make it float on the surface during sintering to improve the feel, while using inorganic copper-chromium-cobalt black and additives for coloring and improving the viscosity in the sintering molten state, it can effectively prevent the migration of the screen-printed conductive silver line on the glass. However, the blackness L value of the ink is relatively high. Summary of the invention
[0005] The purpose of the present invention is to provide a glass powder and a preparation method thereof and application of the glass powder in preparing low-blackness glass ink.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A glass powder, composed of the following components by weight: B 2 O 3 20-30 servings, Bi 2 O 3 30-40 parts, SiO 2 20-30 copies, K 2 O 2-6 parts, BaO 10-15 parts, MgO 3-7 parts.
[0008] In one preferred embodiment, the glass powder, by weight, consists of the following components: 2 O 3 27 copies, Bi 2 O 3 37 parts, SiO 2 25 copies, K 2 O 4 parts, BaO 12 parts, MgO 5 parts.
[0009] In one preferred embodiment, the glass powder, by weight, consists of the following components: B 2 O 3 20 copies, Bi 2 O 3 40 parts, SiO 2 29 copies, K 2 O 4 parts, BaO 12 parts, MgO 5 parts.
[0010] In one preferred embodiment, the glass powder, by weight, consists of the following components: 2 O 3 30 copies, Bi 2 O 3 34 parts, SiO 2 25 copies, K 2 O 4 parts, BaO 12 parts, MgO 5 parts.
[0011] In one preferred embodiment, the glass powder, by weight, consists of the following components: 2 O 3 30 copies, Bi 2 O 3 34 parts, SiO 2 20 copies, K 2 O 5 parts, BaO 15 parts, MgO 6 parts.
[0012] The present invention improves Bi 2 O 3 / B 2 O 3 and Bi 2 O 3 / SiO 2 The ratio of K and sintering process can change the glass network structure, thus affecting the blackness and density of the ink. Different oxides play different roles. 2 O can promote [BO 3 ]The triangle transforms into [BO 4 ] tetrahedron, promoting [BiO 3 ]tetrahedron transforms to [BiO 6 ] octahedron. MgO acts as a network modifier in the glass powder network structure and can be well fused with other oxides in the glass powder. 2 As a network former, its Si-O bond is stable and has a high bond strength, which helps to strengthen the network structure of the glass. BaO, as a sintering aid, can reduce the sintering temperature of ceramics, and at a suitable sintering temperature, it is easy to obtain a suitable blackness. The glass powder prepared by the raw material combination within the ratio range of the present invention helps to improve chemical stability and thermal stability. The blackness L value of the automotive ink prepared from the glass powder is less than 2, and it can perfectly present a uniform color when matched with an organic integrated black ink.
[0013] Based on the same inventive concept, the present invention also claims a method for preparing the glass powder, comprising the following steps:
[0014] B 2 O 3 The temperature is raised to 450-500°C and kept warm; after complete melting, the remaining raw materials are added and the temperature is raised to 1000-1100°C and kept warm. After all the raw materials are melted, water quenching is performed to obtain particles; the particles are ball-milled, dried, and sieved to obtain glass powder with an average particle size of 600-700nm.
[0015] In one preferred embodiment, the B 2 O 3 During the heating process to 450-500°C, the heating rate is 5-15°C / min.
[0016] In one preferred embodiment, the B 2 O 3 Keep warm for 0.5-1h until completely melted.
[0017] In one preferred embodiment, during the heating process to 1000-1100° C., the heating rate is 5-15° C. / min.
[0018] During the heating process, the temperature in the furnace is monitored in real time. A heating rate that is too fast will increase the internal stress of the material, causing deformation or even cracking. Especially when the material is close to the melting point, the impact of a too fast heating rate is more significant. A slow heating rate will lead to uneven temperature distribution, affecting the sintering or melting quality of the material. Reasonable control of the heating rate of the high-temperature furnace can effectively ensure product quality, improve production efficiency, reduce energy consumption and ensure operational safety.
[0019] In one preferred embodiment, the temperature is raised to 1000-1100° C. and maintained for 1-2 hours until all raw materials are completely melted.
[0020] In one preferred embodiment, the medium in the ball mill is zirconium balls.
[0021] In one preferred embodiment, the medium in the ball mill is a mixture of large zirconium balls and small zirconium balls.
[0022] In one preferred embodiment, the diameter of the large zirconium ball is 8-10 mm, and the diameter of the small zirconium ball is 4-5 mm.
[0023] In one preferred embodiment, the mass ratio of particles, water, large zirconium balls and small zirconium balls in the ball mill is 1:3-4:2-3:2-3.
[0024] In one preferred embodiment, the ball milling speed is 150-350 r / min, and the ball milling time is 3-5 h.
[0025] Based on the same inventive concept, the present invention also claims protection for a glass ink, which comprises, by weight: 40-50 parts of the above-mentioned glass powder, 15-30 parts of copper chromium black powder, 5-10 parts of carrier resin, and 5-11 parts of solvent.
[0026] In one preferred embodiment, the glass ink further comprises 1-2 parts of an auxiliary agent.
[0027] In one preferred embodiment, the auxiliary agent includes at least one of a defoaming agent, a leveling agent and a wetting agent.
[0028] In a preferred embodiment, the defoaming agent is an acrylic resin defoaming agent.
[0029] In a preferred embodiment, the leveling agent is polydimethylsiloxane.
[0030] In a preferred embodiment, the wetting agent is a silicone surfactant.
[0031] In a preferred embodiment, the carrier resin is any one of rosin resin, PVB resin, modified ethylene-vinyl acetate resin, and acrylic polyester.
[0032] In one preferred embodiment, the solvent is a mixture of diethylene glycol butyl ether, terpineol and kerosene, wherein the mass ratio of the three solvents is 65-75:15-25:5-15.
[0033] Based on the same inventive concept, the present invention also claims to protect a method for preparing the glass ink, comprising the following steps: mixing the raw materials in proportion, dispersing and grinding, and preparing the glass ink.
[0034] In one preferred embodiment, the particle size of the glass ink is no more than 15 μm, and the viscosity is 5000-10000 mPas.
[0035] Based on the same inventive concept, the present invention also claims protection for the application of the glass ink, which is printing the glass ink on a mobile phone glass back shell, a mobile phone lens or a car glass to obtain an ink layer with a blackness L value less than 2.
[0036] Compared with the prior art, the beneficial effects of the present invention are:
[0037] The present invention can achieve an integrated black effect by adjusting the blackness of the ink, so that the display screen has no obvious boundary with the black frame after the screen is turned off, achieving visual unity. It is the interaction between the various oxide materials and the appropriate proportion between them that makes the perfect combination of low-blackness sintered ink and integrated black ink. These technologies and materials work together to enable the two inks to achieve a visually unified effect while maintaining their respective characteristics. DETAILED DESCRIPTION
[0038] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0039] Example 1
[0040] A glass powder, composed of the following components by weight: B 2 O 3 27 copies, Bi 2 O 3 37 parts, SiO 2 25 copies, K 2 O4 parts, BaO 12 parts, MgO 5 parts.
[0041] Preparation steps:
[0042] The weighed raw materials were put into a mixer and mixed for 0.5 hours to obtain powder, of which B 2 O 3 No addition.
[0043] Add B in high temperature furnace 2 O 3 The temperature was raised to 500°C at a rate of 10°C / min and kept at this temperature for 0.5 hours. 2 O 3 After complete melting, other mixed powders are added, and the temperature is raised to 1100°C at a heating rate of 10°C / min and kept at this temperature for 1 hour to obtain a completely molten glass melt.
[0044] The glass melt is poured into water for quenching to obtain glass particles.
[0045] The glass particles were placed in a ball mill in a ratio of 1:4:3:3 of glass: pure water: large zirconium ball: small zirconium ball, and the ball milling was performed at 200 r / min for 3 hours and 300 r / min for 1.5 hours.
[0046] The diameter of the large zirconium ball is 8-10mm, and the diameter of the small zirconium ball is 5mm.
[0047] After being taken out, the powder was dried in an oven at 100° C. and sieved using a 3000-mesh sieve to obtain glass powder with an average particle size of 685 nm.
[0048] Example 2
[0049] A glass powder, composed of the following components by weight: B 2 O 3 20 copies, Bi 2 O 3 40 parts, SiO 2 29 copies, K 2 O4 parts, BaO 12 parts, MgO 5 parts. The preparation method is the same as that of Example 1.
[0050] Example 3
[0051] A glass powder, composed of the following components by weight: B 2 O 3 30 copies, Bi 2 O 3 34 parts, SiO 2 25 copies, K 2 O4 parts, BaO 12 parts, MgO 5 parts. The preparation method is the same as that of Example 1.
[0052] Example 4
[0053] A glass powder, composed of the following components by weight: B2 O 3 30 copies, Bi 2 O 3 34 parts, SiO 2 20 copies, K 2 O 5 parts, BaO 15 parts, MgO 6 parts. The preparation method is the same as Example 1.
[0054] Comparative Example 1
[0055] Referring to the prior art CN115895332 B, the details are as follows:
[0056] A glass powder, composed of the following components by weight: B 2 O 3 30 parts, SiO 2 5 copies, K 2 O 5 parts, BaO 2 parts, MgO 5 parts, ZnO 60 parts. The preparation method is the same as that of Example 1.
[0057] Comparative Example 2
[0058] Refer to the prior art CN 111333335 B 2# glass powder formula
[0059] A glass powder, composed of the following components by weight: B 2 O 3 15 parts, 15 parts of titanium oxide, 25 parts of silicon dioxide (5 parts of which are in the form of fumed silicon dioxide), 2.5 parts of sodium oxide, 6 parts of boron oxide, 8 parts of zinc oxide, 2 parts of manganese trioxide, 1 part of zirconium oxide, 2.5 parts of yttrium oxide, 1 part of fluorine element, 1 part of metal bismuth powder, and the mesh number of the metal powder is 200-500 mesh. The preparation method is the same as that of Example 1.
[0060] Comparative Example 3
[0061] Referring to the prior art CN 101376561 B, the details are as follows:
[0062] A glass powder, characterized in that the weight percentages of the components are: 63 parts of bismuth oxide, 23 parts of boron oxide, 1.7 parts of zinc oxide, 3 parts of aluminum oxide, 3 parts of silicon oxide, 1 part of magnesium oxide, 0.3 parts of titanium dioxide, 2.6 parts of sodium oxide, 0.4 parts of potassium oxide, 1 part of calcium oxide, 0.5 parts of cerium oxide, and 0.5 parts of lanthanum oxide. The preparation method is the same as that of Example 1.
[0063] Comparative Example 4
[0064] Referring to the prior art CN 103011605 A, the details are as follows:
[0065] A glass powder, composed of the following components by weight: 15 parts of bismuth oxide, 10 parts of zinc oxide, 12 parts of boron oxide, 0.5 parts of aluminum oxide, 6 parts of potassium oxide, 4 parts of sodium oxide, 7 parts of titanium dioxide, 2 parts of calcium oxide, 2 parts of iron oxide, 1 part of chromium oxide, 1 part of copper oxide, and 40 parts of silicon oxide. The preparation method is the same as that of Example 1.
[0066] Comparative Example 5
[0067] A glass powder, composed of the following components by weight: B 2 O 3 27 copies, Bi 2 O 3 37 parts, SiO 2 25 copies, K 2 O4 parts, BaO 12 parts, MgO 5 parts, Li 2 O 5 parts, CaO 2 parts, MgO 2 parts, Al 2 O 3 5 parts. The preparation method is the same as Example 1.
[0068] Comparative Example 6
[0069] A glass powder, composed of the following components by weight: B 2 O 3 27 copies, Bi 2 O 3 37 parts, SiO 2 25 copies, K 2 O4 parts, BaO 12 parts, MgO 5 parts, Fe 2 O 3 8 parts. The preparation method is the same as Example 1.
[0070] Comparative Example 7
[0071] A glass powder, composed of the following components by weight: B 2 O 3 40 copies, Bi 2 O 3 20 parts, SiO 2 29 copies, K 2 O4 parts, BaO 12 parts, MgO 5 parts. The preparation method is the same as that of Example 1.
[0072] Comparative Example 8
[0073] A glass powder, composed of the following components by weight: B 2 O 3 20 copies, Bi 2 O 3 20 parts, SiO 2 49 copies, K2 O4 parts, BaO 12 parts, MgO 5 parts. The preparation method is the same as that of Example 1.
[0074] Comparative Example 9
[0075] A glass powder, composed of the following components by weight: B 2 O 3 20 copies, Bi 2 O 3 40 parts, SiO 2 29 parts. The preparation method is the same as Example 1.
[0076] Comparative Example 10
[0077] A glass powder, composed of the following components by weight: B 2 O 3 27 copies, Bi 2 O 3 37 parts, SiO 2 25 copies, K 2 The preparation method is the same as that of Example 1.
[0078] Comparative Example 11
[0079] A glass powder, composed of the following components by weight: B 2 O 3 27 copies, Bi 2 O 3 37 parts, SiO 2 25 copies, K 2 O 4 parts, BaO 12 parts. The preparation method is the same as that of Example 1.
[0080] Comparative Example 12
[0081] A glass powder, composed of the following components by weight: B 2 O 3 27 parts, SiO 2 25 copies, K 2 O 4 parts, BaO 12 parts, MgO 5 parts. The preparation method is the same as that of Example 1.
[0082] Comparative Example 13
[0083] A glass powder, composed of the following components by weight: B 2 O 3 27 copies, Bi 2 O 3 37 copies, K 2 O 4 parts, BaO 12 parts, MgO 5 parts. The preparation method is the same as that of Example 1.
[0084] The glass powder prepared in the above examples and comparative examples is used to prepare automotive glass ink, including: 40-50 parts of glass powder, 15-30 parts of copper chromium black powder, 5-10 parts of carrier resin, 5-11 parts of solvent, and 1-2 parts of auxiliary agent.
[0085] The additives are defoamer (BYK014), leveling agent (BYK333) and wetting agent (BYK306); the carrier resin is rosin resin (MR-115 / Nissen Forest Chemical).
[0086] The solvent is a mixture of diethylene glycol butyl ether, terpineol and kerosene, wherein the mass ratio of the three solvents is 65-75:15-25:5-15.
[0087] The particle size of copper chrome cobalt black high temperature resistant inorganic pigment is 2-10 microns. When the glass powder and copper chrome cobalt black are fully mixed, it can withstand high temperatures of about 900 degrees Celsius. For specific copper chrome cobalt black, please choose Jiangxi Jinhuan Pigment Co., Ltd.
[0088] The raw materials are mixed in proportion, dispersed and ground, and ground by a three-roll mill, with the particle size controlled below 15 microns and the viscosity between 5000 and 10000 mPas to obtain glass ink. The glass ink is sintered at a sintering temperature of 600 to 700°C.
[0089] The obtained ink layer was tested for performance, as shown in the following table:
[0090] Table 1 Properties of inks prepared from glass powders of Examples 1-4 and Comparative Examples 1-4
[0091]
[0092] Table 2 Performance of inks prepared from glass powders of comparative examples 5-13
[0093]
[0094] The performance of the ink layer after sintering on glass after oxide adjustment in Examples 1 to 4 can meet the low blackness requirement, while the blackness L value of Comparative Columns 1 to 13 is greater than 10, the color is not black enough, does not match the integrated black effect, and does not meet the appearance combination requirement.
[0095] As shown in the above table, it can be seen that: the present invention optimizes the glass powder and adjusts the blackness of the ink to achieve an integrated black effect, so that the display screen has no obvious boundary with the black frame after the screen is turned off, achieving visual unity; in summary, the combination of low-blackness sintered ink and integrated black ink benefits from the application of a variety of oxide materials. These technologies and materials work together to enable the two inks to achieve a visually unified effect while maintaining their respective characteristics.
[0096] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A glass powder, characterized in that: The invention is composed of the following components by weight: 20-30 parts of B2O3, 30-40 parts of Bi2O3, 20-30 parts of SiO2, 2-6 parts of K2O, 10-15 parts of BaO and 3-7 parts of MgO.
2. The method for preparing glass powder according to claim 1, characterized in that: The following steps are involved: The B2O3 is heated to 450-500°C and kept warm; after it is completely melted, the remaining raw materials are added and the temperature is raised to 1000-1100°C and kept warm. After all the raw materials are melted, water quenching is performed to obtain particles; the particles are ball-milled, dried, and sieved to obtain glass powder with an average particle size of 600-700nm.
3. The preparation method according to claim 2, characterized in that: When the temperature of B2O3 is raised to 450-500°C, the heating rate is 5-15°C / min.
4. The preparation method according to claim 2, characterized in that: When the temperature rises to 1000-1100°C, the heating rate is 5-15°C / min.
5. The preparation method according to claim 2, characterized in that: The ball milling speed is 150-350r / min, and the ball milling time is 3-5h.
6. A glass ink, characterized in that: In parts by weight, it comprises: 40-50 parts of the glass powder according to claim 1, 15-30 parts of copper-chromium black powder, 5-10 parts of carrier resin, and 5-11 parts of solvent.
7. The glass ink according to claim 6, characterized in that: The glass ink further comprises 1-2 parts of an auxiliary agent; the auxiliary agent comprises at least one of a defoaming agent, a leveling agent and a wetting agent.
8. The glass ink according to claim 6, characterized in that: The carrier resin is any one of rosin resin, PVB resin, modified ethylene-vinyl acetate resin and acrylic polyester; the solvent is a mixture of diethylene glycol butyl ether, terpineol and kerosene, wherein the mass ratio of the three solvents is 65-75:15-25:5-15.
9. The method for preparing glass ink according to claims 6-8, characterized in that: The process comprises the following steps: mixing the raw materials in proportion, dispersing and grinding the raw materials, and obtaining glass ink.
10. The use of the glass ink according to claim 6, characterized in that: The application is to print the glass ink on a mobile phone glass back shell, a mobile phone lens or a car glass to obtain an ink layer with a blackness L value less than 2.
Citation Information
Patent Citations
Low-melting point lead-less glasses powder for frit slurry, and preparation and use thereof
CN101376561B
Lead-free glass powder for automobile glass printing ink and preparation method of lead-free glass powder
CN103011605A
High-acid-resistance automobile glass ink and preparation method thereof
CN111333335A
A high acid-resistant automotive glass ink and its preparation method
CN111333335B
A kind of smooth low-blackness glass high-temperature ink and its preparation method and application
CN115895332B